Experimental investigation on the effects of magnetic field assistance on the quality of surface finish for sustainable manufacturing of ultra-precision single-point diamond turning of titanium alloys - Hatefi, Shahrokh; Abou-El-Hossein, Khaled (Frontiers in Mechanical Engineering, 2022)
Single-point diamond turning (SPDT) is the state-of-the-art technology for ultra-precision manufacturing of optical products with optical surface roughness down to one nanometer. The SPDT technology has an important role in advanced manufacturing of critical components in different fields of industry. In a SPDT process, different cutting mechanisms affect the optical surface generation and reduce the quality of the turned product. Different efforts have been undertaken to improve the machining conditions as well as optical surface generation mechanisms. Recently, the application of magnetic field assistance in non-conventional SPDT platforms has shown promising results in terms of improving the cutting stability as well as the quality of surface finish. The application of magnetic field assistance becomes more important in SPDT of hard-to-cut materials including titanium alloy. In this study, magnetic field assistance is used in SPDT of Ti-6Al-4V alloy. The machining results show that using this technique could significantly improve the machining conditions and the quality of optical surface generation. The magnetic field assisted SPDT with air coolant could successfully improve the quality of surface finish by 62.5% when compared to non-magnetic purely mechanical SPDT process in dry cutting conditions. Magnetic field assistance is a passive machining technique, environmentally friendly, and it can promote green manufacturing and clean production in ultra-precision SPDT applications.